When perceived innovation job requirement increases employee innovative behavior: A sensemaking perspective. (11th May 2016) - Shin, Shung Jae; Yuan, Feirong; Zhou, Jing
Summary: Building on the sensemaking perspective, we theorize and test conditions under which perceived innovation job requirement increases employee innovative behavior. Using data consisting of 311 employee–supervisor pairs from two companies in China, we found that perceived innovation job requirement had a more positive relation with innovative behavior for employees with low intrinsic interest in innovation than for those with high intrinsic interest. In addition, this positive effect for low‐intrinsic‐interest employees was achieved only when these employees interpreted the job requirement as important either because performance‐reward expectancy was high or because perceived value for the organization was high. We discuss the implications of these results for research and practice. Copyright © 2016 John Wiley & Sons, Ltd.